Isolation and Identification of Bacterial Flora from Internal Organs of Broiler and Their Antibiogram Studies - Roy, Sampa Rani; Rahman, Md Bahanur; Hassan, Jayedul; Nazir, KHM Nazmul Hussain (Microbes and Health, 2013)
The present research work was carried out for the isolation and identification of bacterial flora from internal organs of broiler during the period from January 2012 to June 2012. Ten Hubbard classic broiler bird were purchased from retail market in Mymensingh, Bangladesh. The birds were sacrificed and their liver, lung, esophagus, duodenum and tracheal swab samples were collected (n=50). Using standard bacteriological techniques, Escherichia coli was isolated from 26 (52%) samples. Similarly, Salmonella spp., Staphylococcus spp., Bacillus spp., and Pasteurella spp. were isolated from 15 (30%), 10 (20%), 9 (18%) and 4 (8%) samples, respectively. On the basis of individual sample type, E. coli could be isolated from 8 (80%) duodenum samples being the most prevalent organism. On the other hand, Salmonella spp., Staphylococci spp., Bacillus spp. and Pasteurella spp. were identified in 5 (50%) lungs, 5 (50%) liver, 4 (40%) duodenum and 2 (20%) lungs samples, respectively. Among these isolated bacteria, E. coli was found to be pathogenic for mice. Antibiogram studies revealed that Ciprofloxacin was highly sensitive against all the isolated bacteria. Diversified bacterial species are prevalent in broiler. However, E. coli and Salmonella spp. infection might make the bird vulnerable for easy access of infection. Proper vaccination and use of selective antibiotics are crucial in protecting broilers from these pathogens. DOI: http://dx.doi.org/10.3329/mh.v1i2.14094 Microbes and Health, 2012 1(2): 72-75